2020
DOI: 10.23887/prasi.v15i02.26906
|View full text |Cite
|
Sign up to set email alerts
|

Lexicons of Tabuh Rah Used in Menyali Village

Abstract: This study investigated the lexicons used in Tabuh Rah ceremony in Menyali village. This research was designed in the form of descriptive qualitative study. The focus of this study was to find out lexicons that exist in Tabuh Rah ceremony in Menyali village. The data of this study were obtained by conducting observation and interview with three informants who were from from Menyali village. The object of this study was Tabuh Rah lexicons that exist in Menyali village. The result of this study shows that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 2 publications
2
11
0
Order By: Relevance
“…This study analyzed lexicons. However, this study analyzed lexicons in dance it is in line with research done by previous study that all identified the cultural view of the lexicons in connection with ecolinguistic point of view (Budasi & Satyawati, M, 2021;Kusuma, I, M, A et al, 2020). Fourth, this study also have similarities in the method used descriptive qualitative (Fatimatuzzakrah et al, 2020;Suwonsichon, 2019).…”
Section: Discussionsupporting
confidence: 72%

Lexicons of Song Used in Palawakya Dance

Putu Diandra Dama Suri,
I Gede Budasi,
Putu Eka Dambayana
2023
JPBI
“…This study analyzed lexicons. However, this study analyzed lexicons in dance it is in line with research done by previous study that all identified the cultural view of the lexicons in connection with ecolinguistic point of view (Budasi & Satyawati, M, 2021;Kusuma, I, M, A et al, 2020). Fourth, this study also have similarities in the method used descriptive qualitative (Fatimatuzzakrah et al, 2020;Suwonsichon, 2019).…”
Section: Discussionsupporting
confidence: 72%

Lexicons of Song Used in Palawakya Dance

Putu Diandra Dama Suri,
I Gede Budasi,
Putu Eka Dambayana
2023
JPBI
“…Dancers must be familiar with the lexicon to communicate about Balinese dance in general. The lexicon used in Balinese dance is the most crucial element for instructors to understand when training their students (Budasi et al, 2022;Dewi et al, 2020;Widarta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Language and environment as two things that influence each other. Language change, both in lexicon and grammar, cannot be separated from changes in the natural environment and social (cultural) society (Boddaert et al, 2021;Widarta et al, 2020;Yuniawan et al, 2018). Furthermore, environmental change has an impact on language change, and on the other, society's behavior towards the environment is influenced by the language they use.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the villagers are common people where the communication does not depend on the caste system as other regions in Bali (Sukayana & Putri, 2019;Susandi et al, 2018). The unique phenomenon occurs where the terms of address used by the local people are also different from other regions, for instance; "jero" is a term used for addressing "a person" who has a certain position in the religious social system called Desa Adat in Menyali (Budasi & Satyawati, 2021;Kusuma et al, 2020). It is different from common Balinese addressing terms where "jero" addressed to the common people who marries with the people with caste.…”
Section: Introductionmentioning
confidence: 99%